Regulation of an important glycolytic enzyme, pyruvate kinase, through phosphorylation in the larvae of a species of freeze‐tolerant insect, Eurosta solidaginis. Issue 2 (23rd December 2020) - Abboud, J.; Green, S. R.; Smolinski, M. B.; Storey, K. B.
Abstract: Larvae of the goldenrod gall fly, Eurosta solidaginis, rely on a freeze tolerance strategy to survive the sub‐zero temperatures of Canadian winter. Critical to their survival is the accumulation of polyol cryoprotectants and global metabolic rate depression, both of which require the regulation of glycolysis and reorganization of carbohydrate metabolism. This study explored the role that pyruvate kinase (PK) regulation plays in this metabolic reorganization. PK was purified from control (5 °C‐acclimated) and frozen (−15 °C‐acclimated) larvae and enzyme kinetic properties, structural stability, and post‐translational modifications were examined in both enzyme forms. The Km phosphoenolpyruvate (PEP) of frozen PK was 20% higher than that of control PK, whereas the Vmax of frozen PK was up to 50% lower than that of control PK at the lowest assay temperature, suggesting inhibition of the enzyme during the winter. Additionally, the activity and substrate affinity of both forms of PK decreased significantly at low assay temperatures, and both forms were regulated allosterically by a number of metabolites. Pro‐Q™ Diamond phosphoprotein staining and immunoblotting experiments demonstrated significantly higher threonine phosphorylation of PK from frozen animals while acetylation and methylation levels remained constant. Together, these results indicate that PK exists in two structurally distinct forms in E. solidaginis . In response to conditions mimicking the transition to winter, PK appears to be regulated to support metabolic rate depression, the accumulation of polyol cryoprotectants, and the need for extended periods of anaerobic carbohydrate metabolism to allow the animal to survive whole‐body freezing. Abstract : Pyruvate kinase (PK) was purified from 5 °C control larvae and −15 °C frozen larvae of Eurosta solidaginis . Purified PK from control and frozen insects demonstrated significant differences in kinetic parameters including a lowered maximal activity and lower affinity for the substrate PEP in the frozen group. Immunoblotting demonstrated an increased degree of threonine phosphorylation in frozen group (Image created using BioRender.com ).